Preservation of nasopharyngeal smears for fluorescent antibody detection of Bordetella pertussis. - Harris, P P (1980)
Smears from throat and nasal washings seeded with Bordetella pertussis were either treated with aprotinin (a protease inhibitor) or fixed with 1 or 10% Formalin. These smears were stored at 23, 4, and -70 degrees C. Smears were removed and stained with a fluorescent antibody conjugate for B. pertussis at intervals during 22 days of storage. Results indicate that treatment of smears with 4 or 8 U of aprotinin per ml preserved fluorescent antibody staining qualities of B. pertussis for 22 days; fixation with either concentration of Formalin was unsatisfactory.